Readiness for emergencies and disasters, and health competencies among people with epilepsy - Yılmazel, Gulay (Bangladesh Journal of Medical Science, 2023)
Objective: Epilepsy, one of the chronic diseases with a substantial share in the global burden of disease, can be brought under control with proper disease management. A part of disease management is preparedness for emergencies and disasters. Health competence is a protective mechanism in developing behavior and readiness for emergencies and disasters. This study aims to determine the relationship between preparedness against emergencies and disasters and health literacy competencies in people with epilepsy. Methods: The study was carried out with 270 epilepsy patients, 18 years of age and older, living in Turkey’s Central Black Sea Region between April and May 2022. The questionnaire form included socio-demographic characteristics, health behaviors related to disease management (smoking use, regular exercise, regular use of drugs, etc.), and emergency and disaster preparedness behaviors. The disaster preparedness of the participants was evaluated through the “Disaster Preparedness Scale,” and their health competence skills were evaluated through the “Health Literacy Scale-Short Form. Results: The median HLS-SF score was 30, and the median disaster preparedness score was 31. More than two-thirds of the participants knew the trigger of the seizures and had at least three days of medication with them when they left home. Only 6.7% of the participants stated that they had a medical alert wrist/card, and 37,4% stated that they know the emergency call number they need to call in case of any emergency. The median disaster preparedness scores varied by gender (p<0,01) and were 32 for women and 31 for men. The median disaster preparedness score was 31 for married, and it was found to be significantly higher than for singles (p<0.05). The disaster preparedness score was higher among those who lived in the city/district center (p<0.01). The median disaster preparedness score was 31 among those with regular physical activity, different chronic diseases, and who took their medications regularly, significantly higher than the other groups (p<0.000). There was a significant positive correlation between the individuals’ age, sleep duration, epilepsy duration, HLS-SF, and disaster preparedness levels (p<0.05). Conclusions:People with epilepsy had some gaps in preparedness against emergencies and disasters and also health competence. During a disaster and emergency, medically vulnerable individuals with epilepsy must be able to meet their particular needs on their own. The way to develop emergency and disaster preparedness behaviors is to increase health competencies. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 341-347